Comparative study of immune responses and intestinal microbiota in the gut-liver axis between wild and farmed pike perch (Sander Lucioperca) - Wang, Jing; Li, Shaowu; Sun, Zhipeng; Lu, Cuiyun; Zhao, Ran; Liu, Tianqi; Wang, Di; Zheng, Xianhu (Frontiers in Immunology, 2024)
Diets of wild and farmed fish vary greatly. In this study, we measured various immune parameters in the blood, liver and intestine of wild and farmed pike perch to analyze the effects of variations in diet. Gut microbes were also collected for 16S rRNA gene sequencing. Our results showed that the serum low-density lipoprotein cholesterol (LDL-C) levels were twice as high in the wild group as in the farmed group.Furthermore, the activities of glutamate pyruvate transaminase (GPT) and glutamate oxaloacetate transaminase (GOT) in the intestinal tissues of the wild group were 733.91 U/g and 375.35 U/g, which were significantly higher than those of the farmed group. Expression of IL10 in the liver of farmed pike perch was also 4-fold higher than that of wild pike perch. The expression of genes related to the p53-BAX/Bcl2 signaling pathway was higher in both intestinal and liver tissues of wild pike perch compared with farmed.16S rRNA gene analysis of the gut microflora showed a high relative abundance of Cetobacterium in the gut of farmed pike perch. In conclusion, our study indicated that dietary differences affect glycolipid metabolism and immunomodulation in pike perch.